2021
DOI: 10.1111/sms.14105
|View full text |Cite
|
Sign up to set email alerts
|

Position specific physical performance and running intensity fluctuations in elite women’s football

Abstract: The purpose of the present study was to investigate the physical performance of elite female football players during match play along with transient alterations in running performance following 1-and 5-min univariate peak periods. 54 elite female players from four top-level Norwegian teams were monitored for one season (n = 393 match observations), and physical performance data collected using STATSport GPS APEX. Results revealed significant differences in physical performance between the positions during full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…Regarding its physiological demands, football is an intermittent sport in which an average of 150–250 short, high-intensity actions are performed during the 90 min of the game ( Mohr et al, 2003 ). The average distance covered during a match in women´s football ranges between –8,200–11,000 m among professional-level players, slightly higher in international competitions and minimally lower in collegiate players ( Winther et al, 2022 ). For an exemplary implementation of these demands, cardiorespiratory capacity is a fundamental aspect of the players’ physical condition ( Stolen et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its physiological demands, football is an intermittent sport in which an average of 150–250 short, high-intensity actions are performed during the 90 min of the game ( Mohr et al, 2003 ). The average distance covered during a match in women´s football ranges between –8,200–11,000 m among professional-level players, slightly higher in international competitions and minimally lower in collegiate players ( Winther et al, 2022 ). For an exemplary implementation of these demands, cardiorespiratory capacity is a fundamental aspect of the players’ physical condition ( Stolen et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…One hot topic is the degrees of variability associated with the players’ physical performances across consecutive matches. Recent studies have revealed the importance of analysing the match-to-match variability of locomotor activities (expressed by the coefficient of variation (CV) of a particular measurement) by presenting its practical utility ( Oliva-Lozano et al, 2021 ; Winther et al, 2022 ). The fluctuation of external match load throughout a season should be considered part of the nature of team sports ( Baptista et al, 2022 ), and is influenced by many contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…10 In the Panduro et al study, 9 the games were shown to be intense and impose high physical demands on all outfield players, with high aerobic loading and relevant declines in high-intensity activities toward the end of games. Similarly, Winther et al 11 discussed potential implications for planning of training contents in elite women's football, because during games, transient short peak periods with high amounts of high-intensity actions, including sprinting, accelerations, and decelerations, occur for several playing positions during match play. This means that individualized, position-specific conditioning programs, and physical preparation are warranted in elite women's football.…”
Section: Introductionmentioning
confidence: 99%